Improving The Skills Of Writing Advertising Texts For Class VIII—A Students Of Smpn 16 Mandai Through The Picture And Picture Method - Melianti Melianti; Mayong Mayong; Azis Azis (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. Merlianti 2022. “Improving the Skills of Writing Advertising Texts for Class VIII-A Students of SMPN 16 Mandai Through the Picture and Picture Method